Towards a better understanding of biofoams: Multi-technique characterization of various tannin-furanic foams to assist in material selection for product design - Thomas Sepperer; Giulia Saccomano; Diana E. Bedolla; Raphael J.F. Berger; Primoz Šket; Elena Longo; Gregor A. Zickler; Saeed Borhani; Diego Dreossi; Lisa Vaccari; Maurizio E. Musso; Francesco D’Amico (Materials & Design)
Aiming to sustainable manufacturing options, materials that are discarded from the industry and to which a second life may be given are highly desirable. Condensed tannins constitute the starting point to create tannin-furanic foams, a rigid biobased material that could be a sustainable alternative to those derived from fossil fuel-based chemicals. With the objective of developing novel foam production strategies, three different tannin-furanic foams, namely mechanical, sulfuric and nitric, were thoroughly chemically characterized, and their morphological and macroscopic properties were compared with those of commercial plastic foams made of polystyrene and of polyethylene terephthalate. Understanding the influence of the foaming method on the foam properties is of utmost importance when aiming to substitute existing, well-established products. The chemical characterization was performed by using NMR, FTIR and UV Raman, assisted by DFT quantum mechanics simulations. The morphological characterization was done by Scanning Electron Microscopy and X-ray micro-Tomography. Macroscopic characterization was done by strain–stress, thermal conductivity, and thermal gravimetric analysis. Our studies demonstrated nitric tannin-furanic foams as the closest to an insulating material, while mechanical tannin-furanic foam is more appropriate as a tough material. Overall, they prove that bio-based tannin-furanic foams appear to be a feasible green alternative to conventional plastic foams.